Genetic parameters for growth rate in the fourth generation of selective striped catfish (Pangasianodon hypophthalmus) in Vietnam : - Nelson, Kasigwa Howard (Can Tho University, 2020)
The objective of this study was to estimate genetic parameters of G4 generation, phenotypic and genetic correlations between several traits, harvest body weight, harvest standard body length, specific growth rate, daily weight gain, and survival at harvest in striped catfish (Pangasianodon hypophthalmus). A nested mating design was used to generate G4 generation with 189 full-sib families (from 124 sires and 157 dams). The data set in the G4 generation consisted of 5,506 records for predicted harvest body weight at harvest. Model validation by model fitting (for random effects) concluded the final statistical model that was used to analyze the data for the traits of under investigation. The best model was that which contained random effects of additive genetic and common environment and fixed covariates of the number of days from spawning till tagging (tagage) and the number of days from tagging till the harvest (growage), respectively. A univariate model was used to estimate variance components, while the bivariate model was used to determine genetic correlations using the same model. High heritability estimates were obtained for body weight (0.49-0.61) and harvest standard length (0.43-0.65), which means that harvest body weight proved heritable to utilize the information on the selected candidates. The variation of harvest body weight explains most of the variation of harvest standard body length, and the two traits are genetically positively correlated (rg=0.92-0.94), which permits the efficient indirect selection for standard harvest length (HL) through direct selection for harvest body weight (HW).